CRISPR/Cas9 gene editing: A new therapeutic approach in the treatment of infection and autoimmunity. Issue 8 (28th April 2020) - Mohammadzadeh, Iraj; Qujeq, Durdi; Yousefi, Tooba; Ferns, Gordon A.; Maniati, Mahmood; Vaghari‐Tabari, Mostafa
Abstract: CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR‐associated protein9) may be viewed as an adaptive bacterial immune system. When a virus infects a bacterium, a fragment of the virus genome is inserted into the CRISPR sequence of the bacterial genome as a memory. When the bacterium becomes infected again with the same virus, an RNA molecule that is a transcript of the memory sequence, directs Cas9, an endonuclease, to the complementary region of the virus genome, and Cas9 disables the virus by a double‐strand break. In recent years, studies have shown that by designing synthetic RNA molecules and delivering them along with Cas9 into eukaryotic cells, different regions of the cell's genome can be targeted and manipulated. These findings have drawn much attention to this new technology and it has been shown that CRISPR/Cas9 gene editing can be used to treat some human diseases. These include infectious diseases and autoimmune diseases. In this review article, in addition to a brief overview of the biology of the CRISPR/Cas9 system, we collected the most recent findings on the applications of CRISPR/Cas9 technology for better investigation of the pathogenesis and treatment of viral infections (human immunodeficiency virus infection, hepatitis virus infections, and onco‐virus infections), non‐viral infections (parasitic, fungal, and bacterial infections), and autoimmune diseases.